The role of political institutions in achieving political stability in the Kingdom of Saudi Arabia in light of Vision 2023 - Maysam Ismail; Qasim Alwan Said (Tikrit Journal For Political Science, 2025)
Since the Kingdom of Saudi Arabia launched Vision 2030, numerous institutions have been established in addition to the existing governmental bodies. All these institutions aim to achieve the goals of the vision and enhance its ambitions by using modern and innovative methods, through the utilization of technology and the support of partnerships with the private sector and civil society. These institutions are considered a vital part of the transformation that Saudi Arabia is undergoing. Among the most important institutions in the Kingdom are those in the political, economic, social, and cultural spheres, all working together to achieve the ambitious goals of this vision and to build a more prosperous future for the Kingdom and its citizens.